Research on the Distribution Regularity of Air Volume in the Pipelines of Mining Ventilation Clothing - Bo You; Jiao Yang; Yixin Zhang; Gang Li; Xuemin Zeng; Siqi Wang; Xiao Luo (Geofluids)
In order to study the air volume distribution regularity of mine ventilation clothing, the influence of ventilation clothing of different pipeline structures on air flow distribution is discussed. By establishing the simulation models of three different structures and using software simulation, the air volume distribution under different ventilation air volume and different pipeline structures is analyzed; the relationship between the air volume of the pipelines and the frictional resistance along the course is studied. The results demonstrated that the air volume of the pipelines farther from the ventilation inlet in the transverse type and longitudinal type is larger, while the air volume of the pipelines close to the ventilation inlet is smaller, and the air volume of the intermediate pipelines is medium and relatively stable; regularity of air volume distribution in pipelines: transverse type > spiral type > longitudinal type. Total air volume in the ventilation tubes: spiral type > longitudinal type > transverse type, with the increase of ventilation volume, the air volume in the spiral type tube increases greatly, and a small increase in air volume for transverse type and longitudinal type. Based on the data obtained from the transverse type simulation, the air volume of the pipelines airflow is inversely proportional to the frictional resistance along the course.